Chylous Ascites and Pleural Effusion Treated With Intravenous Octreotide - Ghimire, Subash (Cureus, 2020)
Chylous ascites (CA) is uncommon in cirrhosis. It often presents as diuretic-resistant ascites and is associated with increased mortality. Diagnosis is done by the detection of triglyceride-rich ascitic fluid. There are no published guidelines on the management of CA. We describe the case of a middle-aged female who presented with CA secondary to cirrhosis, and the challenges associated with her treatment and her management with the use of intravenous octreotide.